OPTIMIZE THE DESCA POTENTIAL FOR NEW STUDENTS TO INCREASE THE SELF-CONCEPT IN THE COURSE GEOMETRY - Bistari, Bistari (Universitas Tanjungpura, 2015)
The reasons of this research is to determine the results of a study about the ability of DESCA and self concept new students of Mathematics Education in the course geometry. The method which used in this research is descriptive analysis method. Subjects in this research are students of mathematics education 2014 which take a course of Geometry I in Faculty of Education at the University of Tanjungpura Pontianak. The results showed that among the five aspects of DESCA which gives a good change is the aspect of self-concept. So, it makes the increase of student's self-concept , such as the confidence to expression their ideas and the courage to self recognition and expression of self-concept in geometry classes. Other conditions which conducive to implementation is the correct or incorrect answer is not broken immediately, but for accommodated and analyzed together. Keywords: DESCA, self concept, optimizing